International protection of investments : the substantive standards / August Reinisch, Christoph Schreuer. - Reinisch, August; Schreuer, Christoph (Cambridge University Press, 2020)
This book outlines the protection standards typically contained in international investment agreements as they are actually applied and interpreted by investment tribunals. It thus provides a basis for analysis, criticism, and stocktaking of the existing system of investment arbitration. It covers all main protection standards, such as expropriation, fair and equitable treatment, full protection and security, the non-discrimination standards of national treatment and MFN, the prohibition of unreasonable and discriminatory measures, umbrella clauses and transfer guarantees. These standards are covered in separate chapters providing an overview of textual variations, explaining the origin of the standards and analysing the main conceptual issues as developed by investment tribunals. Relevant cases with quotations that illustrate how tribunals have relied upon the standards are presented in depth. An extensive bibliography guides the reader to more specific aspects of each investment standard permitting the book's use as a commentary of the main investment protection standards.